Agricultural water management practices to improve the climate resilience of irrigated agriculture in India - Sikka, Alok; Alam, Mohammad Faiz; Mandave, Vidya (Wiley, 2022)
The projected implications of climate change for water and agriculture to meet diverse and competitive water demands requires smart water management solutions. Science- and evidence-based, agricultural water management (AWM) can significantly contribute to reduce unsustainable water use and help enhance water resilience and adaptation to climate change. This paper presents a brief overview of potential AWM practices focusing on enhancing water resilience, increasing yields, and wherever possible, reducing emissions. This is achieved via increased land and water use efficiency, water and energy savings, and improved water productivity with considerable scope to improve agricultural resilience. In this context, the prioritization of a location-specific portfolio of smart AWM practices to make the right investment decisions is very important. We present two distinct and complementary approaches to prioritize AWM practices in this paper: one follows stakeholder analysis to build a prioritized portfolio of climate-smart AWM practices and the other employs a simple water balance-based approach to prioritize interventions. The way forward in mainstreaming and scaling out context-specific climate-smart AWM interventions is also discussed with a focus on capacity building, water management extension services, and the mobilization of resources through the convergence of institutions and co-financing from relevant development schemes.